Women, Work, and Birth Rates in Southeastern Europe: A Regional Panel Perspective - Trpkova-Nestorovska, Marija (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2025)
The study explores the interdependence between female labor force participation and fertility dynamics in eight Southeastern European countries during 2000 – 2023, using the crude birth rate as a consistent macro level proxy for fertility in panel regression estimation. The analysis covers eight countries and incorporates economic, educational, and demographic control variables. Results reveal that short-term increases in female employment and tertiary education enrollment are significantly associated with declining birth rates, while economic growth shows a positive effect. Other factors, including part-time employment, urbanization, and parental leave policies, are not statistically significant in the short run. The study underscores the complexity of natality dynamics in transitioning economies and highlights the need for supportive family policies.
Keywords: Birth rates; Female labor force participation; Southeastern Europe; Panel regression; Education; Economic development